2017
DOI: 10.1002/2017ja023861
|View full text |Cite
|
Sign up to set email alerts
|

Current sheets in comet 67P/Churyumov‐Gerasimenko's coma

Abstract: The Rosetta Plasma Consortium (RPC) data are used to investigate the presence of current sheets in the coma of comet 67P/Churyumov‐Gerasimenko. The interaction of the interplanetary magnetic field (IMF) transported by the solar wind toward the outgassing comet consists amongst others of mass loading and field line draping near the nucleus. The draped field lines lead to so‐called nested draping because of the constantly changing direction of the IMF. It is shown that the draping pattern is strongly variable ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…6 we show both responses: the variations of the cometary plasma density and the magnetic field orientation and amplitude along the spacecraft trajectory in the YZ (left panel) and the XZ (right panel) planes in the CSEQ reference frame. On the other hand, the magnetic field rotation observed later, around 1430 UT, together with a very local plasma density increase (not seen in the neutral density, as expected for such a current sheet) is more typical of a solar wind magnetic field rotation, similar to the current sheets reported in Volwerk et al (2017).…”
Section: Magnetic Field Rotation During the Cometary Outburstsupporting
confidence: 73%
“…6 we show both responses: the variations of the cometary plasma density and the magnetic field orientation and amplitude along the spacecraft trajectory in the YZ (left panel) and the XZ (right panel) planes in the CSEQ reference frame. On the other hand, the magnetic field rotation observed later, around 1430 UT, together with a very local plasma density increase (not seen in the neutral density, as expected for such a current sheet) is more typical of a solar wind magnetic field rotation, similar to the current sheets reported in Volwerk et al (2017).…”
Section: Magnetic Field Rotation During the Cometary Outburstsupporting
confidence: 73%
“…There is almost always, i.e., 14 out of 15 events with LAP data, a clear corresponding LAP current response (suggesting a local density increase) associated with the respective magnetic holes; the exception to this is event number 7. However, there is a shift in the density increase in 7 out of those 14 times (see, e.g., Volwerk et al 2017); the density responses are then not strictly anticorrelated with the magnetic field depressions (Figs. 1a and b), but are measured slightly but noticeably after those depressions (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…One of the most characteristic small scale phenomena in the RPC MAG data was the singing comet (Richter et al 2015(Richter et al , 2016, quasi-monochromatic waves within the frequency range of 10 ≤ f sing ≤ 100 mHz. Other small scale structures were also observed, for example current sheets between oppositely directed draped magnetic fields in the coma (Volwerk et al 2017), which are not discussed in this paper.…”
Section: Near Tail -Small Scale Dynamicsmentioning
confidence: 85%
“…That the magnetic field is not well ordered should not come as a big surprise. It was shown that the nested draping in the coma of comet 67P is highly variable, as discussed by Volwerk et al (2017), with the direction of the field changing on the timescale of about 1 h. The coma is much less organized than the fields measured at comet 1P/Halley (see e.g. Riedler et al 1986;Raeder et al 1987), but this may well be an effect from the enormous differences in fly-by velocities of the spacecraft and the huge amount of data available from the ROSETTA mission over a time period of more than two years.…”
Section: Discussionmentioning
confidence: 98%